A Photoenzymatic Strategy for Radical‐Mediated Stereoselective Hydroalkylation with Diazo Compounds. Issue 5 (27th December 2022) - Duan, Xinyu; Cui, Dong; Wang, Zhiguo; Zheng, Dannan; Jiang, Linye; Huang, Wen‐Yu; Jia, Yi‐Xia; Xu, Jian
Abstract: Carbene insertion reactions initiated with diazo compounds have been widely used to develop unnatural enzymatic reactions. However, alternative functionalization of diazo compounds in enzymatic processes has been unexploited. Herein, we describe a photoenzymatic strategy for radical‐mediated stereoselective hydroalkylation with diazo compounds. This method generates carbon‐centered radicals through an ene reductase catalyzed photoinduced electron transfer process from diazo compounds, enabling the synthesis of γ‐stereogenic carbonyl compounds in good yields and stereoselectivities. This study further expands the possible reaction patterns in photo‐biocatalysis and offers a new approach to solving the selectivity challenges of radical‐mediated reactions. Abstract : A photoenzymatic strategy for radical‐mediated stereoselective hydroalkylation with diazo compounds has been developed. By this method, a series of γ‐chiral carbonyl compounds were synthesized in high yields and stereoselectivities.